2015
DOI: 10.1093/scipol/scv055
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the knowledge bases of wind turbine firms in Asia and Europe: Patent trajectories, networks, and globalisation

Abstract: This study uses patent analyses to compare the knowledge bases of leading wind turbine firms in Asia and Europe. It concentrates on the following aspects: (a) the trajectories of key technologies, (b) external knowledge networks, and (c) the globalisation of knowledge application. Our analyses suggest that the knowledge bases differ significantly between leading wind turbine firms in Europe and Asia. Europe's leading firms have broader and deeper knowledge bases than their Asian counterparts. In contrast, Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 34 publications
0
32
0
1
Order By: Relevance
“…Patents citation clustering analysis allows for us to find the core technologies of the leading firms in a global industry and allows for the innovation trajectory of firms and nations to be extrapolated in comparison with other technologies [17,53,54]. It allows for us to discern a technology trajectory based on an analysis of the relevance of existing patents within a firm's portfolio, which can indicate the future of technological innovations.…”
Section: Inter-country Knowledge Flow-based Clustersmentioning
confidence: 99%
“…Patents citation clustering analysis allows for us to find the core technologies of the leading firms in a global industry and allows for the innovation trajectory of firms and nations to be extrapolated in comparison with other technologies [17,53,54]. It allows for us to discern a technology trajectory based on an analysis of the relevance of existing patents within a firm's portfolio, which can indicate the future of technological innovations.…”
Section: Inter-country Knowledge Flow-based Clustersmentioning
confidence: 99%
“…Chen et al [76] provide a detailed account of how the technology base of Chinese OEMs was created and also characterizes the onshore industry evolution using four life-cycle phases framed in the 'business ecosystem lifecycle'. This view is further supplemented in terms of development of intellectual property rights (IPR) and patents by Zhou et al [108]: According to the detailed analysis based on the empirical findings of this research, many of the Chinese OEMs only reached a prototype R+D stage as opposed to serial production, some of the privately funded firms only received a certain level of investment, and others again stopped production after a while after which they exited the market (e.g., Hanwei, Baonan Machine, and Sinovel Wind Group Co., Ltd.).…”
Section: Review Of the Revolutionary Diffusion Of Onshore Wind In Chinamentioning
confidence: 99%
“…One detailed academic analysis comprising 17 WTG OEM firms with a more elaborate perusal of 6 sample firms concluded that based on their first-mover advantages from the European wind market, several European firms seemed to possess the dominant design but later Chinese market entrants caught up to the European firms in terms of number of patents filed on an annual basis [108] which could indicate the emergence of a separate dominant design [26] in the Chinese submarket [27]. One European sub-supplier explained to the associate researcher that " .…”
Section: Secondary Data Collection Efforts: Sub-supplier Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou 외는 아시아 와 유럽의 풍력 발전력 터빈 기업들의 특허동향분석 을 통해 기업간 경쟁력 및 동향을 파악하였다 [11] . 배진 우 외는 키틴유도체 관련 기술에 대한 전세계 특허분 석을 통해 유망 활용 분야 및 우리나라가 나아가야할 R&D 방향을 제시하였다 [12] .…”
Section: 이러한 상황에서 기술에 대한 상세한 정보를 내포하unclassified